Mechanisms Linking Stratospheric Gravity Wave Activity to Hurricane Intensification: Insights From Model Simulation of Hurricane Joaquin - X. Wu; L. Hoffmann; C. J. Wright; N. P. Hindley; M. J. Alexander; X. Wang; B. Chen; Y. Wang; M. Li (Geophysical Research Letters)
Abstract Previous studies based on satellite observations and model simulations have revealed a significant correlation between intense stratospheric gravity wave (GW) activity and hurricane intensification. This research further investigated the underlying mechanism of this correlation by analyzing the properties and propagation characteristics of stratospheric GWs excited by Hurricane Joaquin based on a Weather Research and Forecasting model simulation. By employing the 3‐D Stockwell wave analysis method, we found that GWs excited during hurricane intensification display relatively higher intrinsic frequencies, shorter horizontal wavelengths, and longer vertical wavelengths than during weakening. Analysis of these GWs' propagation using the GROGRAT ray‐tracing model revealed that they can reach the middle stratosphere rapidly within 20 min. This quick propagation enabled the observation of intense stratospheric GWs before the hurricane reached its peak intensity, offering a potential indicator for hurricane intensification. These findings strengthened the basis for considering stratospheric GW activity as a proxy for hurricane intensification under specific conditions.